2021
DOI: 10.48550/arxiv.2108.02699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting the Spectral Features of Ellerman Bombs and UV Bursts. I. Radiative Hydrodynamic Simulations

Jie Hong,
Ying Li,
M. D. Ding
et al.

Abstract: Ellerman bombs (EBs) and UV bursts are both small-scale solar activities that occur in active regions. They are now believed to form at different heights in the lower atmosphere. In this paper, we use one-dimensional radiative hydrodynamic simulations to calculate various line profiles in response to heating in different atmospheric layers. We confirm that heating in the upper photosphere to the lower chromosphere can generate spectral features of typical EBs, while heating in the mid to upper chromosphere can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In general, to ionize silicon into the desired state, a temperature of around 25 kK is necessary in case of local thermal equilibrium, or 80 kK for lower densities (Rutten 2016). A thorough study was performed by Hong et al (2021) who used a 1D radiative hydrodynamic simulation to investigate burst spectra by varying the height and shape of heating in their models. Their simulations of Si iv, a Mg triplet line, and Mg ii k allow us to directly compare our observations, at least qualitatively because the authors already concluded that the very broad Si iv and Mg ii spectra cannot be reproduced because of the limitations of 1D modeling.…”
Section: Comparison To Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, to ionize silicon into the desired state, a temperature of around 25 kK is necessary in case of local thermal equilibrium, or 80 kK for lower densities (Rutten 2016). A thorough study was performed by Hong et al (2021) who used a 1D radiative hydrodynamic simulation to investigate burst spectra by varying the height and shape of heating in their models. Their simulations of Si iv, a Mg triplet line, and Mg ii k allow us to directly compare our observations, at least qualitatively because the authors already concluded that the very broad Si iv and Mg ii spectra cannot be reproduced because of the limitations of 1D modeling.…”
Section: Comparison To Modelsmentioning
confidence: 99%
“…Fe ii, Ni ii) superimposed on the burst spectra. Their exact height is debated (Judge 2015), but they likely occur a few hundred kilometers above the solar surface with recent modeling efforts placing them in the mid to upper chromosphere (Hansteen et al 2019;Hong et al 2021). No coronal emission was identified by Peter et al (2014), thus restricting the events to the "lower" (meaning below the transition region) solar atmosphere, similar to the so-called Ellerman bombs (EBs, Ellerman 1917;Georgoulis et al 2002).…”
Section: Introductionmentioning
confidence: 99%